KADAR OKSALAT DAN KARAKTERISTIK FISIKOKIMIA TEPUNG UMBI TALAS (Colocasia esculenta) AKIBAT FERMENTASI ALAMI - Yuliana Erning Indrastuti; Susana Susana; Dodi Iskandar; Tata Yudhi Wardana (AGROINTEK, 2021)
The effect of fermentation period on the pH, titratable acidity, calcium oxalate, oxalic acid, moisture, ash contents, swelling power, solubility, and color of the taro flours was investigated present research. For this aim, taro corms were cleaned, peeled, washed, sliced into chips. Taro chips were fermented at 0, 24, 48, and 72 hours, drained, dried in a cabinet dryer at 60 °C for 10 h, and ground. Results showed that pH, ash content, solubility, lightness (L *) decreased, and moisture content, titratable acidity dan swelling power increased markedly due to fermentation. Calcium oxalate and oxalic acid of the flours changed 843,83-412,07 mg/100 g and 370,52-949,17 mg / 100 g flour respectively. The fermentation at 48 h effected a significant reduction in calcium oxalate (51,19%) and oxalic acid contents (64,35%). The present study indicated that the taro’s flours oxalate content and physicochemical characteristics properties of the taro flours were significantly affected by the fermentation period.